Underlying Differences Between Chinese Omnivores and Vegetarians in the Evaluations of Different Dietary Groups - Qirui Tian (Frontiers in Psychology, 2019)
Drawing upon self-categorization theory, the present research investigated the attitudes of omnivores and vegetarians toward five dietary groups, including omnivores, conscientious omnivores, semi-vegetarians, vegetarians, and vegans. When they had high (vs. low) meat rationalization, omnivore participants had fewer negative attitudes toward and more positive evaluations of the omnivore groups but more negative attitudes toward and fewer positive evaluations of the vegetarian groups. Vegetarian participants had the most negative attitudes toward the omnivore group, followed by the conscientious omnivore group, the semi-vegetarian group, the vegetarian group, and the vegan group; the vegetarian participants with high meat rationalization (vs. those with low meat rationalization) had more positive evaluations of the omnivore groups. Such findings suggested that high levels of meat-eating rationalization predicted more favorable attitudes toward omnivores among both omnivore and vegetarian participants.